TEACHERS’ PERCEPTION ON REFLECTIVE TEACHING PRACTICE IN ENGLISH FOREIGN LANGUAGE (EFL) CLASSROOM: A CASE STUDY OF ENGLISH NOVICE TEACHER - Hutauruk, Desi Ramadali (ELP (Journal of English Language Pedagogy), 2024)
The aim of this research was to explore the perceptions of English novice teachers regarding reflective teaching practices in EFL classrooms in rural schools. The study employed a qualitative description with a case study design as the research method, and data collection was conducted online through semi-structured interviews and reflective journals with five English novice teachers selected through convenience sampling at the secondary school level. The findings revealed that novice English teachers had positive perceptions regarding the implementation of reflective teaching practices. English novice teachers applied some reflective practices in their teaching, but some practices proved challenging for them due to a lack of understanding, limited preparation time, and a lack of collaboration with peers, hindering them from engaging in more effective reflective practices. Therefore, it can be concluded that the implementation of reflective teaching practices by English novice teachers in rural schools was less effective in developing the quality of their teaching. This study suggests that teacher education programs, especially for English teachers, and schools should equip prospective teachers with adequate understanding and support. This can be achieved through structured training programs, mentoring initiatives, and learning communities to prepare future English teachers for a successful teaching career in rural settings by fostering effective reflective teaching practices.